2020
DOI: 10.1074/jbc.ra120.014615
|View full text |Cite|
|
Sign up to set email alerts
|

E3 ubiquitin ligase PARK2, an inhibitor of melanoma cell growth, is repressed by the oncogenic ERK1/2-ELK1 transcriptional axis

Abstract: Malignant melanoma, the most aggressive form of skin cancer, is characterized by high prevalence of BRAF/NRAS mutations and hyperactivation of extracellular signal-regulated kinase 1 and 2 (ERK1/2), mitogen-activated protein kinases (MAPK), leading to uncontrolled melanoma growth. Efficacy of current targeted therapies against mutant BRAF or MEK1/2 have been hindered by existence of innate or development of acquired resistance. Therefore, a better understanding of the mechanisms controlled by MAPK pathway driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Moreover, the inhibition of the BRAF-ERK1/2 axis increases PARK2 expression. The authors showed that overexpression of PARK2 in melanoma cells was associated with an antiproliferative effect and cell death in vitro and in vivo [ 61 ]. Thus, the reactivation of PARK2 may be an effective approach to counteract melanoma progression.…”
Section: E3 Enzyme Involvement In Melanomamentioning
confidence: 99%
“…Moreover, the inhibition of the BRAF-ERK1/2 axis increases PARK2 expression. The authors showed that overexpression of PARK2 in melanoma cells was associated with an antiproliferative effect and cell death in vitro and in vivo [ 61 ]. Thus, the reactivation of PARK2 may be an effective approach to counteract melanoma progression.…”
Section: E3 Enzyme Involvement In Melanomamentioning
confidence: 99%
“…Few pieces of evidence regarding Elk1 in proteasome inhibitor resistance have been published up to this day; however, the interaction between ERK1/2-Elk1 and the proteasome has already been proven (110). A study about…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the underlying mechanism for this, we predicted the target genes of miR-340-3p and focused on ELK1 as a potential target gene. ELK1 is a transcription factor that can be activated by the MAPK/ERK pathway, further activating the transcription of downstream genes such as c-Fos, cancerous inhibitor of protein phosphatase 2A (CIP2A) [ 26 ], and the E3 ubiquitin ligase PARK2 [ 27 ], and can also interact with other proteins such as thyroid transcription factor FOXE1 or aPKC-iota to co-regulate TERT and aPKC expression, respectively [ 28 , 29 ]. ELK1 plays a crucial role in the development of human cancers.…”
Section: Discussionmentioning
confidence: 99%